PENGUJIAN PECKING ORDER HYPOTHESIS DAN MANAGERIAL HYPOTHESIS - Go, Lisa Safira; Mudji Utami (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
This research examines hypotesis that suitable with capital expenditure behavior of services industry in Indonesia. Pecking Order Theory argued that capital expenditure affected mainly from internal cash flow. However, managerial hypothesis argued that managerial ownership also affect capital expenditure amongst firms and on several cases the effect more keen that internal cash flow. The research uses 25 firms from Jakarta Stock Exchange from 2000-2005. The result showed lower managerial ownership will tend to increase the over-investment by managers, therefore the relationship between managerial ownership to capital expenditure. Meanwhile the research alos found a negative relationship between dividend to capital expenditure and align with Pecking Order Hypothesis.